2016
DOI: 10.1177/0959354316656062
|View full text |Cite
|
Sign up to set email alerts
|

Toward a philosophical history of psychology: An alternative path for the future

Abstract: Recent transformations in the history of science and the philosophy of science have led historians of psychology to raise questions about the future development of their historiography. Although there is a dominant tendency among them to view their discipline as related to the social turn in the history of science, there is no consensus over how to approach the history of psychology methodologically. The aim of this article is to address the issue of the future of the historiography of psychology by proposing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 77 publications
3
33
0
5
Order By: Relevance
“…These analyses suggest that the largest single contributor to the doing is "Sociology" (as indeed was recently observed by Araujo, 2017). However, two other categories also rise above two standard deviations from the mean: "Psychology, Multidisciplinary" and "Psychiatry."…”
Section: Resultssupporting
confidence: 71%
“…These analyses suggest that the largest single contributor to the doing is "Sociology" (as indeed was recently observed by Araujo, 2017). However, two other categories also rise above two standard deviations from the mean: "Psychology, Multidisciplinary" and "Psychiatry."…”
Section: Resultssupporting
confidence: 71%
“…Mais especificamente, tratase de interrogar os documentos a partir de questões filosóficas específicas (ontológicas, epistemológicas, metodológicas, etc.) associadas a tais projetos, atentando para o contexto original de seu surgimento e posterior desenvolvimento (Araujo, 2017a(Araujo, , 2017b. No caso de Tetens, em que a psicologia está inserida em sua filosofia, essa estratégia nos permite explicitar a trama conceitual e os princípios teóricos de seu projeto psicológico, revelando, assim, sua motivação essencialmente filosófica.…”
Section: Métodounclassified
“…Intellectual aspects of the history of psychology, however, are not reducible to social ones. Araujo (2017), for example, has shown that, however undoubtedly important, social approaches to Wundt's psychological program cannot explain alone many of its conceptual developments, such as the abandonment of the unconscious.…”
Section: Implications For the History Of Psychology As A Wholementioning
confidence: 99%